2014
DOI: 10.1254/jphs.13253fp
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 5-HT3 and 5-HT4 Receptors in the Regulation of Circadian Clock Gene Expression in Mouse Small Intestine

Abstract: Abstract. Several lines of evidence suggest that 5-HT receptors play a critical role in the expression of clock genes in the suprachiasmatic nucleus, the main circadian oscillator in hamsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…These results suggest that NRF may promote diurnal expression of intestinal clock genes and downstream clock-controlled genes through microbial-driven serotonin in growing rabbits. To further verify this hypothesis, a rhythmic addition of serotonin in vitro experiment was performed to reveal that serotonin can induce the diurnal expression of clock and tight junction genes in RIEC, and promote cell proliferation, which was consistent with previous findings (Aoki et al, 2014;Spohn et al, 2016). Thus, these results partially confirm that microbial-driven serotonin signals, as one of the zeitgebers, regulate clock gene expression in growing rabbit intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results suggest that NRF may promote diurnal expression of intestinal clock genes and downstream clock-controlled genes through microbial-driven serotonin in growing rabbits. To further verify this hypothesis, a rhythmic addition of serotonin in vitro experiment was performed to reveal that serotonin can induce the diurnal expression of clock and tight junction genes in RIEC, and promote cell proliferation, which was consistent with previous findings (Aoki et al, 2014;Spohn et al, 2016). Thus, these results partially confirm that microbial-driven serotonin signals, as one of the zeitgebers, regulate clock gene expression in growing rabbit intestinal epithelial cells.…”
Section: Discussionsupporting
confidence: 86%
“…Body temperature, as an important zeitgeber, can activate cAMP-response element binding protein (CREB) through the Ca 2+ -CaM signaling pathway mediated by the temperature sensor TRPV4, thereby binding to the cAMP response element (CRE) located at the PER1/2 promoter and initiates gene expression (Buhr et al, 2010;Shibasaki et al, 2015). Similarly, serotonin activates CREB through G protein-coupled receptor-mediated cAMP-PKA signaling pathway, thereby initiating PER1/2 expression (Noda et al, 2004;Lee et al, 2010;Aoki et al, 2014). These results suggest that whether the microbial-driven serotonin is synchronized with the diurnal oscillations of body temperature may influence diurnal rhythmic expression of intestinal clock genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety-five percent of 5-HT in the human body is distributed in the intestine and secreted by intestinal chromaffin cells . Dysregulation of intestinal flora can lower 5-HT levels and then affect the activity of the hypothalamus and other brain regions, eventually causing circadian disruption . Our results showed that GTP effectively ameliorate the disturbance of gut flora caused by circadian rhythm disorder.…”
Section: Discussionmentioning
confidence: 66%
“…Specific primer pairs (see Table 1) were designed using Primer3 Input (version 0.4.0). Real-time RT-PCR was executed under the following conditions: cDNA Synthesis at 42°C for 15 min, followed by 95°C for 2 min, PCR amplification for 40 cycles with denaturation at 95°C for 5 s, and annealing and extension at 60°C for 20 s (9). The relative levels of the target gene PCR product were normalized to those of 18S ribosomal RNA.…”
Section: Short Communicationmentioning
confidence: 99%